Differential contributions of peripheral and central mechanisms to pain in a rodent model of osteoarthritis - Haywood, Adrian R.; Hathway, Gareth J.; Chapman, Victoria (Nature Publishing Group, 2018)
The mechanisms underlying the transition from acute nociceptive pain to centrally maintained chronic pain are not clear. We have studied the contributions of the peripheral and central nervous systems during the development of osteoarthritis (OA) pain. Male Sprague-Dawley rats received unilateral intra-articular injections of monosodium iodoacetate (MIA 1mg) or saline, and weight bearing (WB) asymmetry and distal allodynia measured. Subgroups of rats received intra-articular injections of, QX-314 (membrane impermeable local anaesthetic)+capsaicin, QX-314, capsaicin or vehicle on days 7, 14 or 28 post-MIA and WB and PWT remeasured. On days 7&14 post-MIA, but not day 28, QX-314+capsaicin signfcantly attenuated changes in WB induced by MIA, illustrating a crucial role for TRPV1 expressing nociceptors in early OA pain. The role of top-down control of spinal excitability was investigated. The mu-opioid receptor agonist DAMGO was microinjected into the rostroventral medulla, to activate endogenous pain modulatory systems, in MIA and control rats and refex excitability measured using electromyography. DAMGO (3ng) had a signifcantly larger inhibitory effect in MIA treated rats than in controls. These data show distinct temporal contribtuions of TRPV1 expressing nociceptors and opioidergic pain control systems at later timepoints.